Transgression in the Bengali avant-garde: the poetry of the hungry generation - Cappello, Daniela (Heidelberg Asian Studies Publishing (HASP), 2024)
Transgression in the Bengali Avant-Garde wants to introduce the Hungry Generation movement to a global audience through its poetry, manifestoes and other literary materials. Emerged from the cities of Patna and Calcutta in the early 1960s, the Hungry Generation gained international attention after the poets' arrest on charges of obscenity in 1964. Fiercely provoking the literary establishment, these Bengali bohemians used poetry and literature as means of cultural radicalism, tackling subjects like sexuality, perversion, alcohol and drug consumption, masturbation, and hyper-masculinity to challenge bourgeois morality and respectability. The book sheds light on a variety of Hungryalist sources and explores the literature of the Hungry Generation through the filter of 'transgression', showing how this concept unfolded in the language, aesthetics and culture behind this Bengali avant-garde movement. Furthermore, the book will delve into the poetry of some iconic representatives of the Hungry Generation, critically reading their oeuvre in the context of changing models of sexuality, consumption, and modernization in post-colonial India.